Fertigation in the production of camu camu (Myrciaria dubia HBK Mc Vaugh) at the experimental station of the IIAP, Ucayali, Peru - Abanto, Carlos (2011)
The work was developed in the plot Y1 of Institute of Amazonian Research Peruana-IIAP Ucayali, located between latitudes 8 º 22 '31''south latitude and 74 º 34' 35'' west longitude and altitude of 154 m. It has a soil with low fertility Ultisols (organic matter 1.4%, phosphorus 0.4ppm, potassium 25ppm, pH 4.58, high aluminum content of 6 meq/100 g and CIC of 6.72 meq/100 g of soil). The objective was to determine the phenology and fruit yield candid plant of camu camu of 7 years of age from a mixture of seeds, using 5 treatments by the technique of fertigation through a drip irrigation system (RG). We used a randomized complete block design (RCBD) with 3 replications of 5 treatments and 15 experimental units with 15 floors each, the treatments were T0 [Without irrigation and fertilization], T1 [Drip irrigation without fertilization], T2 [60-40-80/NPK more RG], T3 [120-80-160/NPK more RG], T4 [240-160-320/NPK more RG]. To standardize the material is made of fructification pruning and defoliation manual. We evaluated the reproductive phenology, flower buds No. of No. of small fruits, fruit No. of harvest, fruit weight in g and t.ha-1 performance. It was possible to standardize the phenological stages of outbreaks of issuance until the harvest ending the production cycle in 205 days. The results show no statistically significant differences, it was finally determined that the T2 was 4.8 t.ha-1 doubling the T0 which makes it more cost effective than other treatments.